2019
DOI: 10.2147/cia.s189760
|View full text |Cite
|
Sign up to set email alerts
|

<p>Delirium after hip hemiarthroplasty for proximal femoral fractures in elderly patients: risk factors and clinical outcomes</p>

Abstract: Background The primary aim of the present study was to verify the potential risk factors for developing a delirium after hip fracture surgery. The secondary aim of this study was to examine the related clinical outcomes after a delirium developed post-hip fracture surgery. Patients and methods Data were extracted from a prospective hip fracture database and completed by retrospective review of the hospital records. A total of 463 patients undergoing hip fracture (hip he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 30 publications
12
78
0
Order By: Relevance
“…In terms of demographics, patients suffered from postoperative delirium were significantly older than those without. This was highly consistent with previous studies which had identified advanced age as a common independent predictor of postoperative delirium [1,9,20,21,22,23,24,25].Interestingly, there was significant difference of race distribution between the two groups, indicating a racial difference in occurrence of postoperative delirium. Our study found that the Whites occupying a larger proportion in the postoperative delirium group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In terms of demographics, patients suffered from postoperative delirium were significantly older than those without. This was highly consistent with previous studies which had identified advanced age as a common independent predictor of postoperative delirium [1,9,20,21,22,23,24,25].Interestingly, there was significant difference of race distribution between the two groups, indicating a racial difference in occurrence of postoperative delirium. Our study found that the Whites occupying a larger proportion in the postoperative delirium group.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in order to prevent postoperative delirium, it is critical to understand the risk factors before surgery. Logistic regression was applied and the results were consistent with previous publications [1,9,20,21,22,23,24,25].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Patients now often have multiple concurrent conditions, 4 and frequently develop complications during a hospital stay. 5,6 Comorbidity indices such as Charlson's 7 or Elixhauser's 8 have been widely used as standard methods for risk adjustment in a number of settings. 1,9,10 Importantly, although "comorbidities" and "risk" are often used as synonym terms, these actually refer to different concepts, the former being only one of the components of the latter.…”
Section: Introductionmentioning
confidence: 99%